The role of sustainability living labs in understanding food-water-energy nexus challenges and solutions in India and Jordan - Karin Küblböck; Ines Omann; Hannes Grohs; Raphael Karutz; Christian Klassert; Bernd Klauer; Yuanzao Zhu; Heinrich Zozmann; Mikhail Smilovic; Steven Gorelick (Austrian Foundation for Development Research (ÖFSE), 2021)
There are a multitude of challenges confronting resource-limited, rapidly growing cities that revolve around food-water-energy (FWE) resource issues, and there are a multitude of potential solutions. But such solutions often address one or just a few challenges without regard to their impacts on the entire FWE system. We report on an innovative stakeholder engagement concept that links a living lab approach with the development of an integrated multi-agent urban-FWE systems model for two study regions: Pune, India and Amman Jordan. The model captures connections and feedbacks among the FWE sectors and aims to support long-term policy planning for a more sustainable and equitable provision of food, water and energy. In this context, knowledge of local stakeholders with regard to the FWE nexus is key. Moreover, stakeholder participation increases the chance that the model results are useful for and therefore used by policy makers and other relevant stakeholders, and consequently that the model supports efforts for achieving greater equity and sustainability in the FWE-nexus sectors. We have implemented a two-stage sustainability living lab process (2SLL), embedding several characteristics of existing living lab approaches, and adapting it to the requirements of our effort in Jordan and India. This paper presents the objectives of stakeholder engagement within FUSE, differentiating between model-related and process-related objectives, and discusses requirements for reaching those objectives: First, workshop preparation was key. For one to two months, members of our team were in the study regions, and were able to select a representative cross section of workshop participants. Second, professional facilitation of the workshops was essential in bringing together stakeholders from many different sectors with scientists from different disciplines, and for creating an environment in which the stakeholders were able to formulate their food-water-energy challenges and to propose solutions. Third, an interdisciplinary research team was essential to be able to translate workshops results into inputs for different parts of the systems model. We conclude that the 2SLL process shares many of the characteristics of the classical living labs, such as collaboration between scientific and societal actors, embeddedness in real-world contexts and use of experimentation and learning. However, the 2SLL process adds to these approaches by engaging stakeholders to co-formulate the model and ultimately evaluate the viability of solutions aimed at meeting the multitude of present and future food-water-energy challenges.
Keywords: 330; food-water-energy nexus; multi-agent modelling; urban sustainability; living labs; sustainability living labs; urban living labs; transdisciplinary research; policy evaluation; stakeholder engagement; systems modelling